Human Anelloviruses: Prevalence and Clinical Significance During Pregnancy - Kyathanahalli, Chandrashekara; Snedden, Madeline; Hirsch, Emmet (Frontiers in Virology, 2021)
Although the bacterial microbiota of various compartments (e.g. vagina, amniotic fluid, and placenta) have been studied in pregnancy, there has been far less emphasis on normal and pathological viral communities. Cumulative evidence shows the presence of a number of apathogenic viruses in various tissues of healthy people, including pregnant individuals. What role, if any, these viruses play in human physiology is unknown. Anelloviruses (family Anelloviridae) are circular, single-stranded DNA viruses commonly detected with high prevalence in vertebrate hosts, including primates. Humans are nearly always colonized with at least 1 of 3 anellovirus subtypes, namely Alphatorquevirus (torque teno virus, TTV), Betatorquevirus (torque teno midi virus, TTMDV), and Gammatorquevirus (torque teno mini virus, TTMV). In healthy pregnant people, the prototype anellovirus, TTV, has been found in maternal and (variably) fetal blood, amniotic fluid, cervical and vaginal secretions, breast milk, and saliva. Nonetheless, the relevance of human anelloviruses in pregnancy and labor is unclear. There is evidence suggesting a link between anellovirus colonization and preterm birth. In this review, we discuss what is known about this family of commensal viruses in health and disease, and specifically the roles they might play during pregnancy and in the timing of delivery.